ANALISIS FAKTOR YANG MEMPENGARUHI GAYA KEPEMIMPINAN PERGURUAN TINGGI SWASTA DI KOTA PONTIANAK - Lestary, Asti; Barata, Juliahir (Jurnal Ekonomi STIEP ( JES ), 2020)
Background this study that of pts 19 who institusinya have accredited, only seven institutions ( about 37% ) have accredited b ( that was good categorry ) wholly are located in the Pontianak.This condition is allegedly affected by several factors and the internal conditions institutions such as leadership style, the quantity and quality of teachers, availability of supporting deliver pengeloaan administration and order and institutions.Refer of a whole factors, the researchers believed that the authority factors affecting the institutions is leadership style. Although other supporting factors available and adequate, but a style of leadership that is not a right actually make available resources be made of no effect. A style of its own leadership determined by a variety of factors influence it. Methods used in this study is the quantitatif approach to technique data processing using regression analysis. The factors causing as variable 1 ) situation; 2) experience and vision of leader: 3) vision (the foundation of education ); 4), communication and 5 ) cultural organization and leadership style as variable bound. The research results show that simultaneously all of these issues having a level the influence of as much as 0,947 ( extremely powerful category with the influence of as much as 89,8 %.